A Nutrition Environment Measure to Assess Tribal Convenience Stores: The THRIVE Study. Issue 3 (May 2020) - Wetherill, Marianna S.; Williams, Mary B.; Taniguchi, Tori; Salvatore, Alicia L.; Jacob, Tvli; Cannady, Tamela; Grammar, Mandy; Standridge, Joy; Fox, Jill; Spiegel, Jennifer; Blue Bird Jernigan, Valarie
In rural American Indian (AI) communities, where supermarkets are rare, tribally owned and operated convenience stores are an important food source. Food environment measures for these settings are needed to understand and address the significant diet-related disparities among AIs. Through a tribal-university partnership that included tribal health and commerce representatives from two Native Nations in rural southeastern Oklahoma, we developed the Nutrition Environment Measures Survey for Tribal Convenience Stores (NEMS-TCS) to inform the development and evaluation of a healthy food retail intervention. The NEMS-TCS assessed four scored domains of the rural convenience store food environment—food availability, pricing, quality, and placement—and included 11 food categories that emphasized ready-to-eat food items. Trained raters administered the NEMS-TCS using a sample of 18 rural convenience stores (primarily ranging between 2, 400 and 3, 600 square feet). We assessed interrater reliability with kappa statistics for dichotomized variables and intraclass correlation coefficients (ICC) for continuous variables. NEMS-TCS demonstrated high inter-rater reliability for all food categories (>85% agreement), subscores (ICC = 0.73-1.00), and the total score (ICC = 0.99). The NEMS-TCS responds to recent calls for reliable measures for rural food environments and may be valuable for studying food environments of large convenience stores in other Native Nations as well as other rural settings.